Pengaruh Biaya Periklanan Terhadap Volume Penjualan Studi Kasus pada PT Ramayana Lestari Sentosa, Tbk. Cabang BTM Bogor - Sulistiono, Angga; Jayadi, Rangga (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2011)
Each company wants to grow and develop. Therefore, the company must perform an act thatâs able to provide the progress for itself in the year to come by doing a variety of advertising that will be able to increase the sales.The purpose of this study is to find out how the shape of the advertising done by PT Ramayana Lestari Sentosa Tbk., BTM branch. Besides, how its sales, and how the relationship between advertising and sales volume. The study was conducted at PT Ramayana Lestari Sentosa Tbk., BTM Branch, thatâs kown as R-7. PT Ramayana Lestari Sentosa Tbk., BTM brabch, is engaged in retail. The analytical method used is collecting data from the company itself and interviewing the internal experts of the company: manager, asst. Manager, supervisor, and KC. The result of using correlation analysis shows that thereâs high significant relationship between the advertising and the sales volume, where the correlation coefficient is 0,94. Besides, by using regression analysis, it comes to Y = 5633,59 + 0,35 X. It means that if additional costs for advertisement amount to Rp1.000.000,00, it will make change of income or sales as high as 0,35 times. And by using two sides test of significance of correlation coefficient, it comes to t-count (2,28)